Policies to promote social and solidarity economy: A case study of Mexico City - Juan José Rojas Herrera; Roberto Ca\~nedo Villarreal (United Nations Research Institute for Social Development (UNRISD), 2020)
The paper aims to deepen understanding of the design and implementation processes of public policies to promote the social and solidarity economy (SSE) in Mexico City (CDMX) during the period 2016-2019, and to propose general guidelines to improve and refine them. The paper is based on a review of published materials and field research. The main findings include the following: (a) policies to promote SSE are maintained largely because of legal and institutional inertia and the pressure of social demands to combat unemployment; (b) owing to serious budgetary and staffing constraints, the Ministry of Labour and Employment Promotion (STyFE), which is responsible for implementing the provisions of the Law on the Social and Solidarity Economy (LESS), only serves the cooperative sector and not the whole range of associations recognized as an integral part of the social sector of the economy; (c) little is being done to implement or refine the legal framework; (d) between 2015 and 2018, modest results were achieved, which were marred by the mismanagement (by officials and beneficiaries) of resources and programmes intended to support SSE; (e) in 2019, within the framework of the self-styled "republican austerity", there was a major administrative centralization of the programmes, accompanied by mass layoffs of employees and instructors, the inexperience of the new authorities and the establishment of new 2shell" cooperatives; and (f) the shortcomings of government efforts to guide and channel the transformative and innovative potential of SSE were evident throughout the period under review. Recommendations: (a) immediately align the legislation applicable to SSE enterprises with the Local Constitution and the comprehensive reform of the Law on Cooperative Development of the Federal District (LFCDF); (b) prepare a reliable and updated directory of cooperatives; (c) make all administrative processes simple, flexible and transparent; (d) establish a georeferencing procedure for each cooperative that provides real-time status updates; (e) develop multi-year programmes to achieve long-term goals; (f) tackle intergroup conflicts in the management of institutional spaces; (g) coordinate the public bodies involved in the implementation of public policies - the Government of Mexico City (GCDMX) and the municipalities; (h) set lower quantitative targets than in 2019, giving priority to qualitative aspects (capacity-building and technical support for cooperatives) over quantitative aspects (number of cooperatives formed or strengthened); (i) adopt a standardized training methodology for the formation and strengthening of cooperatives; (j) ongoing evaluation of programmes by institutions that are external to GCDMX; (k) revive the Advisory Council for Cooperative Development of the Federal District (CCFCDF) as an institutional space for dialogue and decision-making with the cooperative movement; (l) encourage research and diagnostic assessments on the conditions in which cooperatives operate and consider, in the light of evidence-based research, the possibility of extending public policy beyond the cooperative sector.
Keywords: 330; Sozialwirtschaft; Mittelstandspolitik; Kommunalpolitik; Mexiko-Stadt; Mexiko